Association of Selective Serotonin Reuptake Inhibitors with Transfusion in Surgical Patients. (July 2016) - Sajan, Farrah; Conte, John V.; Tamargo, Rafael J.; Riley, Lee H.; Rock, Peter; Faraday, Nauder
Abstract : BACKGROUND: The clinical relevance of chronic exposure to selective serotonin reuptake inhibitors (SSRIs) to transfusion in surgical patients is unclear. METHODS: We conducted a prospective cohort study involving patients undergoing cardiac, vascular, spinal, and intracranial surgery at 2 academic medical centers. Medication use, demographics, comorbidities, and laboratory values were determined at baseline by patient interview and review of medical records. The primary outcome was transfusion of any hemostatic allogeneic blood product (i.e., fresh frozen plasma, platelets, and/or cryoprecipitate) through postoperative day 2. RESULTS: The study sample consisted of 767 patients; 364 patients (47.5%) underwent cardiac surgery and the remainder underwent noncardiac surgery. Eighty-eight patients (11.5%) used SSRIs preoperatively. Among cardiac patients, the absolute number of allogeneic transfusions was higher for SSRI users than nonusers (2 [0–6] vs 0 [0–2], median [25%–75%], respectively, P = 0.008), and a similar trend was observed for noncardiac surgery. After adjusting for covariates using ordinal logistic regression, preoperative SSRI use was associated with an approximately 2-fold (odds ratio, 2.2; 95% confidence interval, 1.2–3.98) increase in odds of exposure to allogeneic hemostatic blood products; similar results were observed using propensity score adjustment (odds ratio, 1.85; 95% confidence interval, 1.11–3.07). A significant interaction between SSRI use and surgery type, age, sex, or concurrent antiplatelet therapy was not found; however, heterogeneity in magnitude of effect could not be excluded. CONCLUSIONS: Preoperative use of SSRIs is associated with increased exposure to allogeneic hemostatic blood products in surgical patients at high risk for perioperative bleeding. Determining whether perioperative continuation or withdrawal of SSRIs produces a net clinical benefit requires randomized controlled trials. Abstract : Published ahead of print May 6, 2016